Successful surgical treatment of epithelioid hemangioendothelioma involving multiple liver lesions and bilateral lung nodules. (2022) - Akizawa, Takatora; Nishizawa, Tomotaka; Yamada, Sho; Ota, Hiroki; Kida, Gen; Tsukahara, Yuta; Nakamura, Tomohiko; Oba, Tomohiro; Yamakawa, Hideaki; Kawabe, Rie; Sato, Shintaro; Akasaka, Keiichi; et al.
Abstract: Epithelioid hemangioendothelioma (EHE) affects many organs, particularly lung and liver, and typically presents as multiple lesions. Treatment for EHE is not yet standardized, but surgery is appropriate when lesions are resectable. In our patient, radiography revealed multiple bilateral pulmonary nodules, and CT showed several liver tumors. The liver masses and those in the right lung were removed during the initial surgery; pathology of hepatic specimens confirmed the diagnosis of EHE. During the second operation, the left lung nodules were excised, and all were EHEs. Surgical removal of multiorgan multinodular EHE is a viable treatment option, especially for young patients.